'Which part of my group do I represent?': disability activism and social media users with concealable communicative disabilities. Issue 3 (17th February 2023) - Bitman, Nomy
ABSTRACT: Social media provides marginalized activists multiple options for constructing alternative narratives that challenge mainstream discourse. However, despite these platforms' increasing accessibility, disabled activists may struggle in creating their counter-narrative. Their inability to conform to able-bodied notions of activism leaves their individual experiences out of the discussion of social media activism. This paper addresses this gap by presenting the individual decision-making process of disabled social media users regarding activists' performances in social media as gleaned from the qualitative analysis of in-depth interviews. This process includes three phases that demonstrate the experiences of social media users with communicative concealable disabilities – autistics, hard-of-hearing (HoH), and people who stutter. First, these interviewees present a spectrum of perceptions of disability activism in social media. Second, these perceptions lead to a spectrum of motivations, which mirror the interviewees' various risk-benefit calculations regarding public self-disclosure as disabled. Third, these perceptions and motivations are manifested through interviewees' strategic design of their activist performances in private and public spheres. By rethinking key concepts in social media activism – risk-benefit calculation, slacktivism, and digital storytelling – this process illustrates taken-for-granted assumptions of personalization, visibility and representation, that challenge current discussions on social media activism.